Covid-19 and severe OAT syndrome with dramatic recovery - Simon Robinson; Chadi Elhasnaoui; Jas Kalsi (Archives of Renal Diseases and Management - Peertechz Publications, 2022)
We describe a young man of 37 years with a transient but marked Oligoasthenoteratozoospermia (OAT) syndrome due to severe covid infection with the perfect recovery of semen parameters along with recovery of general health.  Setting district general hospital: Intervention none. We review the role of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2 virus), the role of Angiotensin-Converting Enzyme 2 (ACE-2), Angiotensin 1-7 (Ang 1-7) and propose that it is potentially involved in a cause and effect mechanism of injury.